Online learning modes: synchronous and asynchronous / Naemah Abdul Wahab... [et al.] - Abdul Wahab, Naemah; Othman, Jamal; Kadar, Rozita; Warris, Saiful Nizam (Unit Penulisan Dan Penerbitan JSKM, 2022)
The implementation of online learning in the Malaysian higher education landscape has become vital since the outbreak of the COVID-19 pandemic beginning from March 2020 in Malaysia. In line with the Standard Operating Procedure (SOP) set by the government in all sectors including education and maintaining social distancing to prevent the spread of COVID-19, higher education institutions in Malaysia has converted the traditional face-to- face education system to online learning modes which consist of synchronous and asynchronous mode. This article looks into the definition of synchronous and asynchronous e-learning modes, the technologies used and key issues for each mode, the best practices as well as strengths and also weaknesses of synchronous and asynchronous online learning gathered from previous studies. The aim of this article is for the educators to comprehend more clearly about these two modes of online learning and selecting preferable teaching methods, online tools as well as digital educational resources in improving the quality of the educational process. By blending synchronous and asynchronous modes, educators can create an effective online distance learning experience that are favorable by instructors, but most importantly, ideal to the learners.